1998
DOI: 10.2190/v8bl-gbjk-tlfp-r321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music on the Perception of Paintings

Abstract: This study tested the influence of musical style on observers' perceptions of representational and abstract paintings. Participants were thirty-six male and thirty-six female undergraduates who viewed eight paintings under one of three listening conditions: matching, non-matching, or no music. Participants rated each painting on four semantic-differential scales. Mean ratings were compared using MANOVAs. An interaction of painting style and listening condition (Wilks' lambda = .780, p < .05) showed particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 9 publications
3
22
0
Order By: Relevance
“…The second aim of this study was to replicate the previous findings that (a) paintings followed by congruent music were preferred compared to an incongruent situation [12,13,15]; and that (b) generally, background music induces higher aesthetic ratings of paintings compared to the "silent" situation [15].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The second aim of this study was to replicate the previous findings that (a) paintings followed by congruent music were preferred compared to an incongruent situation [12,13,15]; and that (b) generally, background music induces higher aesthetic ratings of paintings compared to the "silent" situation [15].…”
Section: Introductionmentioning
confidence: 71%
“…Previous studies suggested that certain melodies are regularly associated with particular colors: while "sad" music (minor key) dominantly induces associations of blue, "happy" music (major key) is usually associated with yellow [10,11]. Other studies, which investigated the interaction of different styles or genres of music and visual arts (e.g., paintings and architecture) have found that the stylistic congruence between paintings and music increased the aesthetic evaluation [12,13]. For instance, paintings of Kandinsky are preferred while jazz music is playing in the background, whereas William Turner's paintings are preferred when followed by classical music [14].…”
Section: Introductionmentioning
confidence: 99%
“…Neperud (1982) found that women showed less preference for artistic patterns than men, whereas men rate figurative, i.e., realistic, and abstract styles more favourably than women (see Polzella, 2000). In contrast, Farrell & Rogers (1982), Limbert & Polzella (1998), Lindauer (1990), and Koning & van Lier (2013) each found no evidence of gender differences. Besides, we are aware of no study reporting gender differences in the simultaneous presentation of music and paintings.…”
Section: Discussionmentioning
confidence: 93%
“…In exp. 1 we tested the first part of our hypothesis, based both on common sense and on the findings of other empirical studies (Koning & van Lier, 2013;Limbert & Polzella, 1998), that classical music is a good fit for figurative art, and jazz music for abstract art. We employed a wide selection of figurative and abstract paintings and 40 excerpts of instrumental classical and jazz music and asked participants to rate paintings' pleasantness combined either with classical music or jazz, or viewed in a silent condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation